The Phenomenon of Social Oppression According to Adam Podgórecki - Przylepa-Lewak, Agata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
Adam Podgórecki was one of the most outstanding Polish sociologists of the second half of the 20th century. One of the issues that he has comprehensively analysed was the problem of human-induced social oppression. This concept was understood as an external or internal restriction of the available options of human behaviour with regard to an individual or group of individuals. According to Adam Podgórecki, not only does oppression affect the cognitive options of the available types of behaviour and expands the possibilities of human behaviour (as these can be legal and illegal), but it also limits, sometimes in the literal sense, the physical possibilities of behaviour. Moreover, it can often occur inadvertently. An interesting aspect of his theory is pointing to the fact that law often becomes the main mechanism of social oppression. The aim of the article is to present the phenomenon of social oppression in A. Podgórecki’s view, which may help eliminate it from social life. At first, the essence of social oppression according to Adam Podgórecki will be explained, followed by a presentation of related phenomena, the significance of the law for the phenomenon of social oppression, and a description of the methods used to study it. The article has been written using the method based on the analysis of the available literature on the subject, critical analysis of A. Podgórecki’s works, and the historical method.